(untitled) (University of Khartoum Engineering Journal, 2022)
Telemedicine is having a great impact in the monitoring of patients located in remote nonclinical environments, e.g. [1]& [2]. Due to the development and widespread use of the mobile phones, it is becoming possible and feasible to apply this technology to be an integral part of telemedicine systems. This paper discusses the design, implementation and testing of the ECG transmission system over GSM network. Using this transmission system, ECG signals are transmitted in real time from the patients’ location in a remote clinical or nonclinical environment to the specialists in hospitals or clinics using the capabilities of the GSM network. This system is intended to be used primarily for diagnosis purposes, thus eliminating or reducing the trouble taken by many patients to travel vast distances to be seen by the cardiologists. The transmission system design is implemented using a combination of hardware and software components. The transmitter implemented in this study can interface with existing ECG machines or may acquire analogue signals directly from lower end ECG probes. The signal at the receiving end could be displayed on an oscilloscope or on a PC. The prototype system built during the course of this study has successfully transmitted a representative ECG signal over the GSM system and a replica signal was also successfully recovered at the receiving side. The transmitter and receiver hardware is intended to be low cost and light in weight so that it may also be implemented as a portable device usable in home care facilities.